(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article is devoted to examining the necessity of introducing the polluter pays principle into the environmental law system of the Republic of Uzbekistan, as well as highlighting its beneficial and significant aspects. The importance of this principle, which is widely applied in many developed countries, is thoroughly discussed, and its advantages are demonstrated through several practical examples. In order to assess the feasibility of applying this principle in the Republic of Uzbekistan, information is provided on its key advantages and effectiveness. The principle is also analyzed from the perspective of human rights. Particular attention is paid to the effectiveness of this principle in addressing the current environmental situation within the territory of the Republic. The author seeks to discuss the relevance of this issue based on scientific and theoretical foundations and to conduct an in-depth study.